2021
DOI: 10.1021/jasms.0c00443
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Quantification of Carboxymethyllysine-Modified Peptides in Human Plasma

Abstract: A prolonged hyperglycemic condition in diabetes mellitus results in glycation of plasma proteins. N(ε)-Carboxymethyllysine (CML) is a well-known protein advanced glycation end product, and one of its mechanisms of formation is through further oxidation of Amadori compound modified lysine (AML). Unlike enrichment of AML peptides using boronate affinity, biochemical enrichment methods are scarce for comprehensive profiling of CML-modified peptides. To address this problem, we used AML peptide sequence and site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Enrichment of glycated peptides/glycopeptides prior to LC-MS/MS analysis is important because of their relatively low abundance. Borate/boronate affinity purification is popular for glycated peptides, and dozens to hundreds of glycated proteins have been identified in human serum and plasma [ 108 - 110 ]. Recently, AGE antibodies have been produced, providing an exciting way to analyze plasma protein AGEs [ 111 ].…”
Section: Analytes and Corresponding Sample Preparation Methods In Pla...mentioning
confidence: 99%
“…Enrichment of glycated peptides/glycopeptides prior to LC-MS/MS analysis is important because of their relatively low abundance. Borate/boronate affinity purification is popular for glycated peptides, and dozens to hundreds of glycated proteins have been identified in human serum and plasma [ 108 - 110 ]. Recently, AGE antibodies have been produced, providing an exciting way to analyze plasma protein AGEs [ 111 ].…”
Section: Analytes and Corresponding Sample Preparation Methods In Pla...mentioning
confidence: 99%
“…This study quantified 58 modified peptides from 19 proteins with 57 sites. Five modified peptides were significantly higher in poor glycemic control compared to good control (Korwar and Zhang, 2021). In a different study on T1D, another AGE, modification with glyoxal (also shown in Figure 4), was studied on histones.…”
Section: Diabetes Biomarker Discoverymentioning
confidence: 99%